2016
DOI: 10.1080/19490976.2016.1138197
|View full text |Cite
|
Sign up to set email alerts
|

Impact of probiotic supplements on microbiome diversity following antibiotic treatment of mice

Abstract: Shifts in microbial populations of the intestinal tract have been associated with a multitude of nutritional, autoimmune, and infectious diseases. The limited diversity following antibiotic treatments creates a window for opportunistic pathogens, diarrhea, and inflammation as the microbiome repopulates. Depending on the antibiotics used, microbial diversity can take weeks to months to recover. To alleviate this loss of diversity in the intestinal microbiota, supplementation with probiotics has become increasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(69 citation statements)
references
References 59 publications
4
65
0
Order By: Relevance
“…configuration, the absence of a microbiome under extreme germ-free condition (Zmora et al, 2018) resulted in preferential and sustained probiotic colonization, pointing toward the indigenous microbiome as a major driver of colonization resistance to these administered strains in the murine gut environment. Less extreme microbiome depletion by broad-spectrum antibiotic treatment in mice only mildly improved probiotics coloni-zation, suggesting that human compatibility of the examined probiotic strains, or other uneradicated microbial factors, may contribute to murine colonization resistance in this setting, in line with a previous report (Grazul et al, 2016). Humans, in contrast, feature highly diverse microbiome configurations (Yatsunenko et al, 2012, Zeevi et al, 2015, driving an individualized capacity of homeostatic colonization of the 11 probiotic strains ( Maldonado-Gó mez et al, 2016, Goossens et al, 2006Zmora et al, 2018).…”
Section: Discussionsupporting
confidence: 84%
“…configuration, the absence of a microbiome under extreme germ-free condition (Zmora et al, 2018) resulted in preferential and sustained probiotic colonization, pointing toward the indigenous microbiome as a major driver of colonization resistance to these administered strains in the murine gut environment. Less extreme microbiome depletion by broad-spectrum antibiotic treatment in mice only mildly improved probiotics coloni-zation, suggesting that human compatibility of the examined probiotic strains, or other uneradicated microbial factors, may contribute to murine colonization resistance in this setting, in line with a previous report (Grazul et al, 2016). Humans, in contrast, feature highly diverse microbiome configurations (Yatsunenko et al, 2012, Zeevi et al, 2015, driving an individualized capacity of homeostatic colonization of the 11 probiotic strains ( Maldonado-Gó mez et al, 2016, Goossens et al, 2006Zmora et al, 2018).…”
Section: Discussionsupporting
confidence: 84%
“…All data optimization and analysis were performed by IS Diagnostics Ltd. with the in-house developed software in combination with the Spotfire software package (Tibco). We used a Student's t-test to compare the quantitative 16S PCR analysis between mice [7]. Diversity was calculated with unrarefied data, as rarefication is not relevant to the IS-pro data.…”
Section: Is-profiling Of the Intestinal Microbiomementioning
confidence: 99%
“…Patients receiving antibiotic treatment may develop a dysbiotic gut microbiota, characterized by a shift in dominating phyla, reduced diversity, and intestinal overgrowth of multi-drug resistant or opportunistic pathogens, e.g., Escherichia coli and Enterococcus spp. [3,4,7,8]. Colonization with resistant bacteria causes a risk of infection, especially in patients with co-morbidities [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…The Shannon-Wiener index, which is a measure of alpha diversity, was 3.6-3.7, and was not affected by feeding with the AN1 cells. Although it has been reported that gut bacterial alpha-diversity is important for host health (Thursby & Juge, 2017), the influence of probiotics on alpha diversity varies by study: for example, a diversity increasing effect was reported in an antibiotic-treated gut, and no effect or a decreasing effect was reported on the diversity in normal healthy hosts (Grazul, Kanda, & Gondek, 2016;Laursen et al, 2017). Figure 1 shows the relative abundance in the caecum at the genus level.…”
Section: Direct Cell Counting and Alpha Diversitymentioning
confidence: 99%